The faunal remains from Magogo and Mhlopeni: small stock herding in the Early Iron Age of Natal - Voigt, E. A. (Southern African Humanities, 2021)
The Early Iron Age site of Magogo has yielded one of the best-preserved faunal assemblages for this period in South Africa. For the first time we have been able to identify the remains of both sheep and goats in Natal during the sixth century A.D. Evidence for the presence of cattle also exists, but these animals appear to have been relatively scarce. The assemblage may provide the earliest evidence for domestic dog in South Africa. Nyala are also identified in an area well outside that of their current distribution. A very high proportion of young ovicaprines in the sample may be possible evidence for environmental deterioration. To cite this article: Voigt, E. A. 1984. The faunal remains from Magogo and Mhlopeni: small stock herding in the Early Iron Age of Natal. Annals of the Natal Museum 26 (1): 141-63.